The process of creation through visual methodologies: Use of scientific infographics in the subject of Museography - Pazos-López, Ángel; Sanz Domínguez, Estrella (Eikón / Imago, 2025)
The experience presented here shows the methodology developed for the incorporation of scientific infographics in the study and analysis of museographic projects. Infographics and museography use visuality on different levels, which is a didactic opportunity to create and study through different visual methodologies. The student uses infographics as a tool for the development of creative skills, conceptualization and visual interpretation, also requiring, for its correct execution, to carry out tasks typical of scientific methodology such as prior research, analysis, interpretation and synthesis. The process, as a whole, provides the student with transversal and specific competences of the contents taught, obtaining, in addition, a highly effective means of visual communication.»